تأثير الحرب على سعر الصرف والسياسة النقدية والمالية السورية - سلمان, حيان (Latakia University Journal - Economic and Legal Sciences Series, 2016)
Syria suffers from an unfair war against it for more than four years, involving the forces of old and new Zionist- US colonialism and the Persian Gulf States, Turkey and other allied states. This war affected all aspects on the life of the Syrian community, but I will focus in the research on the economic impact, particularly on the exchange rate of monetary policy and fiscal policy too. I will focus on the exchange rate as it reflects the price of one currency against the other currency or currencies, and I used the dollar exchange rate because it is the most commonly used in Syrian economic transactions, The Syrian pound is linked with the us dollar in 1947 under law No.304/on 2 February 1947 and identified rate of the Syrian pound equivalent to (0, 405513) grams of gold, i.e. (45,6) cents.The importance of exchange rate was revealed with the growing expansion of international commercial exchanges of goods and services, financial transactions, and in the digital language how many of Syrian pounds shall be sold or abandoned to obtain one unit of another currency or USD, for example, so we can notice the importance of exchange rate stability, and therefore one of the most important responsibilities of the monetary policy in Central Bank, is to create an exchange rate that helps to boost economic activity on the macro and micro level and contribute to increase the economic powerتتعرض سورية لحرب ظالمة منذ أكثر من أربع سنوات، ويشارك فيها قوى الاستعمار القديم والجديد والتحالف الصهيوأمريكي ودول الخليج وتركيا وغيرها من الدول التي تدور في فلكها، وأثرت على كل جوانب الحياة المجتمعية السورية سأركز في بحثي هذا على تأثيرها الاقتصادي, وخاصة على سعر الصرف التابع للسياسة النقدية وعلى السياسة المالية أيضا، وسأركز على سعر الصرف لأنه يعبر عن سعر عملة ما مقابل عملة أو عملات أخرى. استخدمنا سعر صرف الدولار لأنه الأكثر استخداما في التعاملات الاقتصادية السورية، وتجدر الإشارة إلى أن الليرة السورية ارتبطت مع الدولار الأمريكي منذ عام 1947بموجب القانون رقم /304/ تاريخ 2/2/ 1947وحدد سعر الليرة السورية بما يعادل(0.405513) غرام ذهب وتعادل( 45.6) سنتا، وقد ظهرت أهمية سعر الصرف مع تزايد وتوسع التبادلات التجارية الدولية للسلع والخدمات والتعاملات المالية، وبلغة رقمية كم من الليرات السورية يجب بيعها أو التخلي عنها للحصول على وحدة واحدة من العملات الأخرى أو الدولار مثلا، ومن هنا يتبين لنا أهمية استقرار سعر الصرف، ولذلك فإن من أهم مسؤوليات السياسة النقدية المتجسدة في البنك المركزي (بنك البنوك)، هو إيجاد سعر صرف يسهم في تفعيل النشاط الاقتصادي علىالمستوى الكلي والجزئي والمساهمة في زيادة القوة الاقتصادية .